Pengembangan Media Edukasi Ular Tangga untuk Pembelajaran Al-Qu’an Hadits - Alya Mafazatul Umamah; Moch. Bahak Udin By Arifin (Indonesian Journal Publisher, 2024)
The snake and ladder game is a simple and common game that can be used as an effective learning medium. The snake and ladder educational medium has been modified for use in Al-Qur'an Hadith lessons. The main purpose of developing this educational medium is to help teachers assess students' understanding of the material that has been explained. The material is taken from the Al-Qur'an Hadith lesson module for Muhammadiyah Elementary School level, which is the main source of the educational media created. The research method used R&D (Research and Development) and the ADDIE research model. This educational Snakes and Ladders media creates a fun learning atmosphere. Students' knowledge can be trained because education is provided through interesting play-based learning activities and is able to improve socialization skills among students.